Effect of different organic amendment on some properties of oasis soil (Saharan region of Touggourt - Algeria) - Abid, Abdelfettah; Boumaraf, Belkacem; Saadi, Ines; Mohammed Berrekbia, (Emirates Journal of Food and Agriculture, 2023)
Local farmers combine several methods to manage soil organic matter: improve the quality and integrate other processes of managing the fertility of cultivated soils. The purpose of this work is to evaluate the effects of different organic amendments (OA) on any physico-chemical properties of the soil such as: pH, electrical conductivity (EC) and organic matter (OM). The amendments are: palm compost and manure (CPM); palm compost and reed (CPR); palm compost and reed + manure (CPRM); ovine manure (Om) and unamended soil (Ctl). The choice of materials is based on the idea of valorizing palm groves waste (palms and reeds) with ovine manure. The trial is conducted on randomized complete block design where two levels of soil samples are taken two months apart: S0 (day zero), Sin (initial sampling before application of amendment) then, S1, S2 and S3 until the end of cropping cycle. Obtained results show that all different OA increase the pH and decrease the EC of the soil after two months of application (S1) compared to the value of the initial sampling (Sin), which demonstrates the very highly significant effect of time on both parameters in the surface horizon. For the OM an incessant increase during the assay period was noticed where Om and CPR have marked the highest values during the third sampling (S3). This proved that the prepared composts from oasian wastes have an effect in improving soil properties over time. From an economic point of view, CPR showed results of OM that are similar of Om, which is considered as the most used and expensive manure in the region. Keywords: Compost; Oasis; Organic amendment; Valorization; Wastes